PERAN KEUTAMAAN ORGANISASI DAN AKUNTABILITAS PUBLIK DALAM MEMENGARUHI KINERJA SEKTOR PUBLIK DI ORGANISASI PERANGKAT DAERAH PROPINSI BANTEN - Dadan Ramdhani (FEB Universitas Sultan Ageng Tirtayasa, 2018)
This study aims to examine the influence of organizational culture, job satisfaction and organizational commitment through public accountability for the performance of public organizations. This study is a replication and development of research conducted by Abdullah and Arisanti Herlin (2010). Object of this study is regional work units (OPD) in Banten province. This study is an empirical study with purposive sampling techniques in data collection. Data obtained by questionnaire which was distributed to the head of each regional work units Banten province, with a questionnaire return rate reaches 83.90% ie 73 respondents. Data analysis was performed with a Structural Equation Model (SEM) with a program SmartPLS (Partial Least Square). Test results show that the hypothesis of the eight hypotheses proposed six hypotheses are accepted. Accepted hypothesis is the hypothesis 1 (significant positive influence Organizational Culture on Performance of Public Organizations.), Hypothesis 2 (a significant positive influence Job Satisfaction on Performance of Public Organizations.), Hypothesis 3 (Organizational Commitment has a positive effect is not significant to the performance of Public Organizations.) hypothesis 4 (Public Accountability is not a significant negative effect on the performance of the Public Organization.), hypothesis 5 (Cultural Organization significant positive effect on Public Accountability.), hypothesis 6 (Organizational commitment significant positive effect on Public Accountability.) and the hypothesis is rejected is the hypothesis 7 (Cultural Organisation no significant negative effect on performance through the Public Accountability of Public Organizations.), hypothesis (Organizational commitment is not a significant negative effect on performance through the Public Accountability of Public Organizations.).